Every leader is an artist how the world's greatest artists can make you a more creative leader - O'Malley, Michael 1954- (McGraw-Hill, 2012)
Every Leader Is an Artist makes the compelling case that many of the attributes that make a person a great leader are actually those that make someone a superior artist: intention, focus, authenticity, skill, and imagination.
Includes bibliographical references and index. - Print version record
Keywords: Leadership